Underestimated disease prevalence and severe phenotypes in patients with biallelic variants: A cohort study of primary familial brain calcification from China. (July 2019) - ,; Huang, Xuerong; Fu, Shaowei; Chen, Wenhai; Huang, Yanbin; Lan, Likang; Zhu, Xiaofen; Xu, Zhijun; Huang, Huayun; Zhou, Lifeng; Chen, Zilong; Lou, Minfang; et al.
Abstract: Background: Primary familial brain calcification (PFBC) is a rare calcifying disorder of the brain with extensive clinical and genetic heterogeneity. Its prevalence is underestimated due to clinical selection bias (compared with symptomatic PFBC patients, asymptomatic ones are less likely to undergo genetic testing). Methods: A total of 273 PFBC probands were enrolled in a multicenter retrospective cohort study by two different approaches. In Group I (nonsystematic approach), 37 probands diagnosed at our clinic were enrolled. In Group II (systematic approach), 236 probands were enrolled by searching the medical imaging databases of 50 other hospitals using specific keywords. Genetic testing of four genes known to be causative of autosomal dominant PFBC was performed in all probands using cDNA. All identified variants were further confirmed using genomic DNA and classified according to ACMG-AMP recommendations. Results: Thirty-two variants including 22 novel variants were detected in 37 probands. Among these probands, 83.8% (31/37) were asymptomatic. Two probands with homozygous pathogenic SLC20A2 variants presented more severe brain calcification and symptoms. Based on the variant detection rate of probands in Group II, we extrapolated an overall minimal prevalence of PFBC of 6.6 per 1, 000, much higher than previously reported (2.1 per 1000). Conclusions: We identified a higher proportion of genetically confirmed PFBC probands who were asymptomatic. These patients would be overlooked due to clinical selection bias, leading to underestimation of the disease prevalence. Considering that PFBC patients with biallelic variants had more severe phenotypes, this specific condition should be focused on in genetic counseling. Highlights: A high proportion of asymptomatic PFBC patients remain undiagnosed in the clinic. We extrapolated an overall minimal disease prevalence of PFBC to 6.6 p. 1000. Biallelic mutations in SLC20A2 caused severe symptoms and brain calcification.